Structural analysis of counter-attacks performed at the 2010 European handball championship for women - Ohnjec, K.; Vuleta, D.; Dizdar, D.; Milanovic, D. (Sport Science - International Scientific Journal of Kinesiology, 2015)
The main goal of this research is to determine the correlation of the type of transition attack (individual, group, collective) in handball game. The sample of entities consisted of 2,710 attacks (respectively 413 counter-attacks) registered at the 2010 European Women's Handball Championship (2010ECh) held in Denmark and Norway. The sample of variables with the associated modalities included: counter-attack type, then the beginning of attack, an outcome of the attack, closure of the attack and the number of passes and attack duration. The transition phase of handball game was realized and conducted at the 2010ECh for women primarily through the performance of group counter-attacks. The teams managed to transform the acquired numerical or spatial advantage over opponents and their yet unorganized defences, usually through the cooperation of 2-5 players, into counter-attacks. The calculated values of ƒÔ2 test indicate that transition attacks . individual, group and collective, significantly differ from each other with respect to the beginnings of attack and to the type of attack closure relative to playing positions, while there were no statistically significant differences between types of counter-attack with respect to the variable attack outcome. The results of Kruskal-Wallis test and ANOVA indicate the statistically significant difference in attack duration and number of passes between individual, group and collective counter-attack.